Cardioprotection against ischemia/reperfusion injury by QiShenYiQi Pill® via ameliorate of multiple mitochondrial dysfunctions - Chen JR; Wei J; Wang LY; Zhu Y; Li L; Olunga MA; Gao XM; Fan GW (Dove Medical Press, 2015)
Jing Rui Chen,1–3 Jing Wei,1–3 Ling Yan Wang,1–3 Yan Zhu,1–3 Lan Li,1–3 Mary Akinyi Olunga,1–3 Xiu Mei Gao,1–3 Guan Wei Fan1–31Tianjin State Key Laboratory of Modern Chinese Medicine, Tianjin, People’s Republic of China; 2Key Laboratory of Pharmacology of Traditional Chinese Medicine Formulae, Ministry of Education, 3Institute of Traditional Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of ChinaAim: To investigate the potential cardioprotective effects of QiShenYiQi Pill® (QSYQ) on myocardial ischemia/reperfusion (I/R) injury through antioxidative stress and mitochondrial protection.Methods and results: Sprague Dawley rats were pretreated with QSYQ or saline for 7 days and subjected to ischemia (30 minutes occlusion of the left anterior descending coronary artery) and reperfusion (120 minutes). Cardiac functions were evaluated by echocardiogram and hemodynamics. Myocardial mitochondria were obtained to evaluate changes in mitochondrial structure and function, immediately after 120 minutes reperfusion. Pretreatment with QSYQ protected against I/R-induced myocardial structural injury and improved cardiac hemodynamics, as demonstrated by normalized serum creatine kinase and suppressed oxidative stress. Moreover, the impaired myocardial mitochondrial structure and function decreased level of ATP (accompanied by reduction of ATP5D and increase in the expression of cytochrome C). Myocardial fiber rupture, interstitial edema, and infiltrated leukocytes were all significantly ameliorated by pretreatment with QSYQ.Conclusion: Pretreatment of QSYQ in Sprague Dawley rats improves ventricular function and energy metabolism and reduces oxidative stress via ameliorating multiple mitochondrial dysfunctions during I/R injury.Keywords: QSYQ, ischemia/reperfusion injury, energy metabolism, mitochondria